Comparison of condylar inclination attained by interocclusal records and radiographic tracing - Sholeh Shahidi; Sadaf Adibi; Mahro Vojdani; Amir Ali Reza Khaledi (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Determination of condylar inclination is very important in dentistry. Condylar inclination is specific for each patient. Inaccuracy registration of condylar inclination can result in problems for posterior teeth disocclusion or multiple occlusal interferences. The aim of this study was to evaluate the relationship between the inclination of posterior slope of articular eminence according to a transcranial radiographic technique and the values obtained from intraoral protrusive bite records.Materials and methods: In this clinical study, 30 patients (13 males and 17 females) with an average age of 20‒40 years, with no sign and symptoms of temporomandibular disorders, were evaluated and two transcranial radiographies were taken from the right and left sides. Outlines of articular eminence, mandibular fossa and postglenoid process were drawn. The most inferior point of articular eminence and posterior glenoid process were named Tb and Pt, respectively. The eminence line was drawn and the angle between eminence line and Pt-Tb line was determined. Protrusive bite records were registered by polyvinylsiloxane. Each patient's cast was mounted in the Denar Mark II articulator; condylar inclination was determined and compared with radiographic values. Pearson's correlation coefficient and independent samples t-test were used for statistical analysis (α=0.05).Results: The means ± SD of posterior inclination of articular eminence were 39.5±5.7 and 38.8±5.4 on the right and left sides, respectively. The mean condylar inclinations ± SD obtained from protrusive bite records were 29.4±4.5 and 30.2±4 on the right and left sides, respectively. A relatively strong linear correlation was observed between the radiographic and protrusive bite records for determination of condylar inclination (p value < 0.05).Conclusion: Under the limitations of the present study it can be concluded that in patients in which determination of condylar inclination by intraoral method is difficult, transcranial radiography can be used for adjusting condylar guidance of articulators; however, further studies are necessary.Key words: Bite registration, Mandibular condyle, Radiography.